2015
DOI: 10.1021/acs.analchem.5b01831
|View full text |Cite
|
Sign up to set email alerts
|

Determination of a Large Set of β-Adrenergic Agonists in Animal Matrices Based on Ion Mobility and Mass Separations

Abstract: While the coupling of traveling wave ion mobility spectrometry (TWIMS) and mass spectrometry is mainly reported for structural purposes, we studied its potential in enhancing compounds analysis such as growth promoters used in livestock animals at trace concentrations. β-Adrenergic agonists have been selected as model compounds since they exhibit a range of close physicochemical properties leading to analytical issues using classical approaches. In this paper, the potential of Synapt G2-S (Q-TWIM-TOF MS) has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…Beucher et al. studied nonsteroidal selective androgen receptor modulators, which are prohibited by the World Anti‐Doping Agency, but remain readily available and potentially used in livestock production for growth promotion . Interestingly, the authors were able to successfully couple SFC separation with TWIMS–MS for the analysis of bovine urine and suggested that CCS has potential within this workflow to be used as an identification parameter within a screening method.…”
Section: Application Of Ion Mobility Spectrometry To the Analysis Of mentioning
confidence: 99%
“…Beucher et al. studied nonsteroidal selective androgen receptor modulators, which are prohibited by the World Anti‐Doping Agency, but remain readily available and potentially used in livestock production for growth promotion . Interestingly, the authors were able to successfully couple SFC separation with TWIMS–MS for the analysis of bovine urine and suggested that CCS has potential within this workflow to be used as an identification parameter within a screening method.…”
Section: Application Of Ion Mobility Spectrometry To the Analysis Of mentioning
confidence: 99%
“…Recently, several analytical methods have been developed for the determination of β -agonist drugs in foodstuffs and animal urine [ 5 13 ]. The analytical methods are mainly based on two different immune analysis techniques [ 6 , 7 , 9 , 11 ] and on the chromatographic technique [ 5 , 8 , 10 , 12 , 13 ]; both have advantages and drawbacks. Immune analysis techniques such as enzyme-linked immunosorbent assay (ELISA) exhibit the features of rapid and simple analysis but come with drawbacks of giving rise to false positives.…”
Section: Introductionmentioning
confidence: 99%
“…β-agonists, a class of phenylethanolamine compounds similar in chemical structures, are widely used for the treatment of respiratory diseases in clinical applications 4, 5 . It has been reported that β-agonists promote animal growth rates and increase muscle leanness by inducing redistribution of fat in the muscle tissues of mammals 68 . Driven by reaping high profits, β-agonists are often illegally fed to animals.…”
Section: Introductionmentioning
confidence: 99%